Review of the genus Pseudoxistrella Liang, 1991 (Orthoptera: Tetrigidae, Metrodorinae) - Storozhenko, Sergey Yu.; Omelko, Mikhail M. (Zootaxa, 2012)
The monotypic genus Pseudoxistrella Liang, 1991 was established for P. eurymera Liang, 1991 from Hainan Island in China (Liang, 1991) as a genus closely related to Xistrella Bolivar, 1909. It was listed by Blackith (1992) and Otte (1997) without definition of subfamily of Tetrigidae. Later Pseudoxistrella was placed in the subfamily Metrodorinae (Liang & Zheng, 1998). But this genus is characterized by the rounder and turned downward posterior angle of lateral lobes pronotum like in subfamily Tetriginae (in Metrodorinae posterior angle truncated and turned outward), therefore now Pseudoxistrella is considered as a genus of uncertain position within subfamilies of Tetrigidae (Eades et al., 2012). A new species of the genus Pseudoxistrella was found in Vietnam. This gives us the possibility to clarify the diagnosis of Pseudoxistrella and its place in the family Tetrigidae.